Optimization of Fraud Potential Prevention in Implementation of National Health Insurance at Puskesmas Abeli - Sartini Risky MS; Asbath Said (Journal of Health Science and Prevention, 2019)
Fraud actions at institutions can catapult health costs. Globally, the potential loss due to fraud is estimated at 7,29% every year. Increasing the number of referrals in advanced health facilities FKTL is an indication of fraud behavior. In Southeast Sulawesi, the referral rate is high, reaching 17% with the maximum ideal standard for the average referral rate of first level health facilities(FKTP) to advanced health facilities(FKTL), not more than 5%. While in Kendari City in 2015, the referral rate from Puskesmas to Abunawas General Hospital was also still high at around 9.5% in 2015 and an increase of 15.3% in 2016. One of the puskesmas that provided referrals was Abeli ​​Community Health Center. This study aims to analyze the potential for fraud prevention in the implementation of National health insurance(JKN) at Abeli ​​Health Center. This study using observational analytic using one group pre test and post test design. Research was conducted at Abeli ​​Health Center and technique used was cluster random sampling with 28 respondents. From the statatistic test results obtained, there were differences in knowledge before and after the intervention with a mean gap value of 0, 21429 with a lower limit of 0.05226 and an upper limit of 37631 and a p value<α (0.011 <0.05). The suggestion in this study is to the health centers and hospitals to increase more understanding of fraud in the implementation of the JKN program by having socialization.